Overview of pre-clinical and clinical studies targeting angiogenesis in pancreatic ductal adenocarcinoma. Issue 1 (10th October 2016) - Craven, Kelly E.; Gore, Jesse; Korc, Murray
Highlights: Pancreatic ductal adenocarcinoma (PDAC) is hypovascular. Vascular endothelial growth factor A (gene: VEGFA) (VEGF-A) is overexpressed in PDAC. Increased VEGF-A or microvessel density is associated with poor patient outcome. Blocking VEGF-A in mouse models reduces tumor volumes and improves survival. Clinical trials targeting angiogenesis elicit marginal survival benefit. Abstract: The importance of angiogenesis in pancreatic ductal adenocarcinoma (PDAC) and its therapeutic potential have been explored in both pre-clinical and clinical studies. Human PDACs overexpress a number of angiogenic factors and their cognate high-affinity receptors, and anti-angiogenic agents reduce tumor volume, metastasis, and microvessel density (MVD), and improve survival in subcutaneous and orthotopic pre-clinical models. Nonetheless, clinical trials using anti-angiogenic therapy have been overwhelmingly unsuccessful. This review will focus on these pre-clinical and clinical studies, the potential reasons for failure in the clinical setting, and ways these shortcomings could be addressed in future investigations of angiogenic mechanisms in PDAC.